2020
DOI: 10.1002/ajmg.a.61900
|View full text |Cite
|
Sign up to set email alerts
|

Chronic subdural hematoma: A previously unreported life‐threatening complication in adult with Sotos syndrome

Abstract: Macrocephaly, defined as head circumference ≥ 2 SDs, is a cardinal feature of Sotos syndrome (SS) and generally persists in adulthood. Subdural fluid collection, typically associated with macrocephaly, is described in children due to anatomical conformation, and in adulthood due to brain atrophy and ex-vacuo hydrocephalus. On the other hand, a true, symptomatic, chronic subdural hematoma (CSH) is a previously unreported complication of SS in adulthood. Here we describe the first SS patient presenting symptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Our two patients, together with the patient reported by Carli et al 5 , indicate that parenchymal hemorrhage and subdural hematoma may be characteristic features of CVDs associated NSD1 abnormality. Given that the precise pathogenesis of CVD is unclear, it is indeed difficult to explain the observed difference of disease onset and CVD phenotype.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Our two patients, together with the patient reported by Carli et al 5 , indicate that parenchymal hemorrhage and subdural hematoma may be characteristic features of CVDs associated NSD1 abnormality. Given that the precise pathogenesis of CVD is unclear, it is indeed difficult to explain the observed difference of disease onset and CVD phenotype.…”
supporting
confidence: 83%
“…We report two patients of Sotos syndrome accompanied by CVDs. To our knowledge, one other patient of Sotos syndrome with CVD has been described who had recurrent chronic subdural hematoma, and harbored a de novo canonical splice site variant in NSD1 (NM_022455.4:c.5892+1G>T) 5 . Collectively, therefore, three of >450 patients of Sotos syndrome showed CVDs (<0.6%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Carli et al previously reported an adult female with Sotos syndrome with recurrent SDH between ages 29 and 30 years. 9 More recently, Itai et al reported a male with subdural hematoma and parenchymal hemorrhage in the posterior lobes in the neonatal period, as well as a 39-year-old woman with evidence of recurrent parenchymal hemorrhage. 10 Park et al additionally reported an infant with Sotos syndrome requiring a subduroperitoneal shunt at 10 months due to a severe subdural hygroma.…”
Section: Discussionmentioning
confidence: 99%